2021
DOI: 10.3390/plants10122630
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Charcoal Rot in Peanut Crop through Strains of Trichoderma spp., in Puebla, Mexico

Abstract: Charcoal rot is an emerging disease for peanut crops caused by the fungus Macrophomina phaseolina. In Mexico, peanut crop represents an important productive activity for various rural areas; however, charcoal rot affects producers economically. The objectives of this research were: (a) to identify and morphologically characterize the strain “PUE 4.0” associated with charcoal rot of peanut crops from Buenavista de Benito Juárez, belonging to the municipality of Chietla in Puebla, Mexico; (b) determine the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Similar mean inhibition was observed by Choudhary et al (2021), where T. harzianum, which restricted the growth of the fungus by 67.59% in relation to the control, stood out. Martínez-Salgado et al (2021) reported the highest percentage of growth inhibition of this phytopathogen (71.11%) by T. koningipsis. According to studies by Paul et al (2021), the antagonism exhibited by T. harzianum ranged between 75.01 and 78.22%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar mean inhibition was observed by Choudhary et al (2021), where T. harzianum, which restricted the growth of the fungus by 67.59% in relation to the control, stood out. Martínez-Salgado et al (2021) reported the highest percentage of growth inhibition of this phytopathogen (71.11%) by T. koningipsis. According to studies by Paul et al (2021), the antagonism exhibited by T. harzianum ranged between 75.01 and 78.22%.…”
Section: Discussionmentioning
confidence: 97%
“…Screening of the antagonist potential of Trichoderma isolates has been demonstrated in scientific works for several plant pathogenic fungi, such as Macrophomina phaseolina (El-Benawy et al, 2020, Choudhary et al, 2021, Martínez-Salgado et al, 2021, Paul et al, 2021; Fusarium spp. (Pellan et al, 2020;Kumar et al, 2021;Yassin et al, 2021); Sclerotium rolfsii (Kotasthane et al, 2014;Kamel et al, 2020;Blanco et al, 2021) and Sclerotinia sclerotiorum (Marques et al, 2016;Amaral et al, 2018;Sumida et al, 2018;Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…with a germination percentage of 90% were used for pathogenicity tests. Plants of 30 days old (10 cm tall and 5 mm in diameter) were individually placed in a plastic pot (1 L) containing a sterilized mixture of peatmoss and Agrellite (1:1 v/v) (Martínez-Salgado et al 2021). The plants were kept under greenhouse conditions (70% RH, 28 °C) in two separate areas.…”
Section: Methodsmentioning
confidence: 99%
“… Manganiello et al (2018) found that the volatile secondary metabolites secreted by T. viride TG050 609 can cause the mycelium of P. nicotianae to grow irregularly, break, or even dissolve, proving that T. viride has an antibiosis effect on P. nicotianae . In addition, most Trichoderma strains can produce antimicrobial substances such as pentaibols, which can inhibit a variety of plant pathogenic fungi and can also cooperate with cell wall-degrading enzymes on pathogenic fungi to effectively inhibit their growth ( Debode et al, 2018 ; Mayo-Prieto et al, 2019 ; Kovács et al, 2021 ; Martínez-Salgado et al, 2021 ; Tamizi et al, 2022 ). Some studies have shown that some Trichoderma spp.…”
Section: Application and Mechanism Of Action Of Trichoderma...mentioning
confidence: 99%